2011
DOI: 10.1111/j.1365-2362.2011.02538.x
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin in juvenile obesity – the effect of obesity intervention and sex

Abstract: Central obesity combined with HI/IR contributes to visfatin elevation. Visfatin association with metabolic/biochemical variables is gender dependent. Diet + enhanced physical activity are effective in visfatin reduction, the degree of which depends on baseline visfatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
3
10
0
1
Order By: Relevance
“…Our results are in line with those reported for other cytokines such as leptin, IL-6 [44], or visfatin [49] in WL intervention studies with obese children from similar age ranges. Although, CT-1 is a protective cytokine, Moreno-Aliaga et al suggested that it could be increased in obesity as a compensatory mechanism to fight against this disease [13].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with those reported for other cytokines such as leptin, IL-6 [44], or visfatin [49] in WL intervention studies with obese children from similar age ranges. Although, CT-1 is a protective cytokine, Moreno-Aliaga et al suggested that it could be increased in obesity as a compensatory mechanism to fight against this disease [13].…”
Section: Discussionsupporting
confidence: 92%
“…The NAMPT is an enzyme that triggers the synthesis of nicotinamide adenine dinucleotide (NAD), which is essential for the functioning of cells β-pancreaticin insulin secretion [2]. As in both cases visfatin may promote reduction of blood glucose, a negative association is suggested between visfatin and insulin resistance [53,54], as observed in our results.…”
Section: Discussionsupporting
confidence: 73%
“…This result was in agreement with a Turkish study that reported plasma visfatin levels of 4.0 (SD 3.0) ng/mL in the obese group and 2.2 (SD 1.5) ng/mL in the non-obese group (p=0.014). 9 Similar results were also found by Araki et al in Japan, 33 plasma visfatin levels in obese children were found to be increased two-fold compared to children with normal BMI. 12 Visfatin is produced by macrophages in fat tissue, especially visceral fat tissue.…”
Section: Discussionsupporting
confidence: 79%